ATM-Dependent Downregulation of USP7/HAUSP by PPM1G Activates p53 Response to DNA Damage - Khoronenkova, S; Dianova, I; Ternette, N; Kessler, B; Parsons, J; Dianov, G (2012)
The deubiquitylation enzyme USP7/HAUSP plays a major role in regulating genome stability and cancer prevention by controlling the key proteins involved in the DNA damage response. Despite this important role in controlling other proteins, USP7 itself has not been recognized as a target for regulation. Here, we report that USP7 regulation plays a central role in DNA damage signal transmission. We find that stabilization of Mdm2, and correspondingly p53 downregulation in unstressed cells, is accomplished by a specific isoform of USP7 (USP7S), which is phosphorylated at serine 18 by the protein kinase CK2. Phosphorylation stabilizes USP7S and thus contributes to Mdm2 stabilization and downregulation of p53. After ionizing radiation, dephosphorylation of USP7S by the ATM-dependent protein phosphatase PPM1G leads to USP7S downregulation, followed by Mdm2 downregulation and accumulation of p53. Our findings provide a quantitative transmission mechanism of the DNA damage signal to coordinate a p53-dependent DNA damage response. © 2012 Elsevier Inc..